ANALISIS MEKANISME CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Sefie Daniswari; Wahyu Meiranto (Diponegoro Journal of Accounting, 2023)
This study aimed to examine the effect of corporate governance mechanisms and financial performance on financial distress in listed manufacturing companies on Indonesian Stock Exchange (IDX). The independent variables used in this study i.e. the size of the board of commissioners, the proportion of independent commissioners, the activity of the board of commissioners, profitability, liquidity, and leverage. The dependent variable was financial difficulties. The population in this study consisted of all manufacturing companies listed on the Indonesian Stock Exchange from 2019 to 2021. The sample was determined by a purposive sampling method. The total sample of this research was 318 company’s financial statements. This study used logistic regression analysis for hypothesis testing. The results of this study indicate that corporate governance, such as the size of the board of commissioners, had a significant effect on financial distress, but the variable proportion of independent commissioners and the activity of the board of commissioners had no significant effect on financial difficulties in manufacturing companies in Indonesia. Financial performance consisting of liquidity and leverage had no significant effect on financial distress, on the other hand profitability had significant effect.